Long Term Survival of Ventricular Septal Rupture (VSR) Closure Concomitant with CABG in Post-Acute Myocardial Infarction Patient - Irien E. Hernawati (Cardiovascular and Cardiometabolic Journal, 2020)
Ventricular Septal Rupture (VSR) is a serious complication of acute myocardial infarction. This incidence continues to decline with the thrombolytic and PCI era, but the mortality rate is still high. VSR occurs most frequently after anterior AMI. VSR can occur in the apical, mid or basal of the septum. The most common location is in the apical portion of the septum. The timing of VSR closure surgery depends on the state of the patient's hemodynamic and VSR diameter. Various studies have suggested that VSR closure concomitant with Coronary Artery Bypass Grafting (CABG) provide a better outcome.